Analysis of e-WOM and Product Quality on Online Purchase Intention Through Brand Image Mediation: (Case Study: Tokopedia Online Buying Interest in Sukabumi City) - Rahmatullah, Irfan; Siwiyanti, Leonita; Sudarma, Ade (Eastasouth Institute, 2025)
This study seeks to examine the impact of Electronic Word of Mouth (e-WOM) and product quality on online purchase intention, with brand image serving as a mediating variable. The focus of the research is users of the Tokopedia e-commerce platform in Sukabumi City. This study uses a quantitative approach by collecting data through questionnaires from 100 respondents who have made at least two purchases on Tokopedia. The data analysis approach employed was the Structural Equation Modelling Partial Least Square (SEM-PLS) method. The findings indicate that electronic word-of-mouth and product quality significantly impact brand image, although do not directly affect online purchase intention. The brand image has been demonstrated to buffer the relationship between e-WOM and product quality with online purchase intention. Positive reviews and a strong brand image increase consumer trust and drive purchase decisions. This research provides practical implications for e-commerce businesses to take advantage of positive reviews, maintain product quality, and build a brand image to increase consumer loyalty.